Assessing the prevalence, sources and selective antecedents of organizational stressors among elite football players and coaches in the Ghana premier league: Empirical evidence for applied practice - Srem-Sai, Medina; Hagan, John Elvis; Ogum, Prosper Narteh; Schack, Thomas (Frontiers in Sports and Active Living, 2022)
Globally, job-related stress has been classified as a health epidemic which is common among many individuals across diverse geographical boundaries. Despite this established knowledge, research has primarily focused on the general population and among health workers. Therefore, understanding stress related experiences in professional sport contexts would help design appropriate stress management interventions for effective coping. The overarching aim of this research was to assess occupational stress related experiences among players and coaches in the Ghana premier league. The study sought to assess: (1) the prevalence and sources of stressors among players and coaches, and (2) how age and years of experience influenced their stress levels. Using a census survey, 44 premier league coaches and 424 players who were officially registered for 17 premier league clubs completed the intensity dimension of the Organizational Stressor Indicator for Sport Performers which had 5 subscales namely: Goals and Development, Logistics and Operation, Team and Culture, Coaching and Selection. Descriptive statistics (means and standard deviation) and multivariate analysis of variance were used to analyze the data. The results revealed that stress was prevalent among football players and coaches, with it being significantly more dominant among coaches, p<.001. Selection was identified as the most predominant stressor for coaches (i.e., selecting players to play) and players (i.e., being selected). Age and experience were found not to be significant predictors of stressors for players and coaches in Ghana. Findings reveal that generally, stress is common among football players and coaches, especially on issues related to selection. Sport psychologists and team managers in the various premier league clubs should incorporate designed interventions (e.g., stress innoculation training) aimed at providing adequate psychological support to promote coaches’ and players’ well-being.